Migraine-Related Stroke - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The diagnosis of migraine-related stroke is reviewed and case histories provided from the Center for Stroke Research, Department of Neurology, Henry Ford Hospital, Detroit, MI.